Role play: the usage of dolls in improving the selfcare skills among autism spectrum disorder individuals with sexual behaviour problems / Mohd Yusof Zulkefli ... [et al.] - Zulkefli, Mohd Yusof; Ibnu, Ireena Nasiha; Mohamed, Shazleen; Sahharon, Hamizah (Universiti Teknologi MARA, Kedah, 2023)
The inability to communicate and express their feelings causes ASD individuals to have issues managing themselves. The point of sexual behaviour among ASD individuals is alarmingly widespread. The sexual behaviour problem among ASD individuals is disturbingly familiar and observable and always happens in schools or public areas. Despite disturbing experiences, ASD individuals eventually do not know the dos and don'ts of appropriate sexual behaviour, especially in modifying sexual behaviour cues. As a result, most instances involving sexual behaviour issues, such as harassment, frequently fail to serve both the victim and the perpetrator owing to a lack of solid proof. Monitoring and preparation for transiting ASD individuals to an adult are needed direly. Therefore, this innovation aims to examine the use of the doll in improving self-control skills among ASD individuals with sexual behaviour problems. In order to support this innovation, a study was conducted for eight weeks with observation methods, pre-test, and post-test conducted on 5 ASD teenagers range 15 to 18 years. The study's results found an improvement in ASD individuals' self-care skills achievement after using a doll as a role-play self-representative. The implication of this study shows that ASD individuals can learn to manage themselves better and be more aware after using a doll as a role-play.